The role of diastolic outward current deactivation kinetics on the induction of spiral waves. - Kogan BY; Karplus WJ; Billett BS; Pang AT; Khan SS; Mandel WJ; Karagueuzian HS (Pacing & Clinical Electrophysiology, 1991)
The mechanism of induced reentry in an initially homogeneous repolarization matrix still remains undefined. In the present study we hypothesized that the slow deactivation rate of the delayed outward current (dIo/dt), which occurs during diastole after complete repolarization, can cause activation failure and facilitate reentry. We modeled the excitation-recovery process using the modified FitzHugh- Nagumo equations in a two-dimensional medium of 128 by 128 cells using the Connection Machine (CM-2), a massively parallel computer that is highly suitable for this class of problem. The model was one cell thick, uniformly excitable, and isotropic. When the rate of Io deactivation was slowed to yield action potential duration (APD) restitution curves similar to experimentally observed arrhythmic ventricular muscle cells APD restitution curves, premature stimulation (S2) induced nonstationary double spiral waves (Figure 8 reentry). A decrease in dIo/dt increased the radius of the circle around which the tip of the spiral waves rotates and decreased its angular velocity. Wave fronts propagated through areas where the residual diastolic lo was fully inactivated and blocked in areas where its amplitude was high. No such dynamics of wave front propagation could be induced when S2 was applied after the completion of Io deactivation. We conclude that the kinetics of deactivation of the Io during diastole has a profound influence on the dynamics of two-dimensional wave front propagation. The similarities of the APD restitution curve implemented in the computer model with slow deactivation of lo and that observed in our canine model of quinidine induced ventricular tachyarrhythmias suggest that lo deactivation kinetics may play an important role in arrhythmogenesis in the intact ventricle.